A study of the effect of outdoor exposure on the impact strength of plastics - มิ่งบรรเจิดสุข สิริวรรณ (Bulletin of Applied Sciences, 2022)
In this study, the changes in impact strength of two types of plastics due to natural outdoor exposure were investigated. Determinations of impact strength of the materials weathered at Bangkok, Thailand exposure site were performed every three months for a period of one year. It was found that each material had different patterns of the changes in their impact properties. Impact strength values of poly(acrylonitrile-butadiene-styrene) decreased highly in the first three months and the decreases were gradually slow down afterward. At 317 days of exposure time, impact strength retention was 50%. Polycarbonate, another type of plastic, had the decreases in impact strength values less than 10% of the original value during the first 6 months of the whole exposure time. When the exposure time approached 233 days, impact strength was close to 50% of its original value. Starting from the ninth month, impact strength was lost more than 80%. By using the information obtained in this study, poly(acrylonitrile-butadiene-styrene) could then be assessed as being a more durable material to outdoor environment exposure than polycarbonate.